(untitled) (Training and Practice : Journal of Educational Sciences, 2011)
Book and literature are means of transmitting values and maintaining mental health. Reading books is always something special. While it enriches us with experiences, our problems and the stress case. Reading, as an intellectual activity, sets our mental and emotional layers in motion, stimulates our inner activity and „reinforces the self” at the same time. Reading reglures silence. What was read can only be spoken about after some time has passed, because for a while we go on living in the book, breathe together with the characters, suffer or feel glad. Nevertheless the number of people reading books is decreasing very fast. According to a survey conducted by Ferenc Gereben reading sociologist, more than half of the adult population do not read one book a year. Interest towards reading and fiction is radically decreasing, although there is much to be said for it: it enriches our vocabulary, shows who we are, forms our personality, enriches our behavioural customs, shows us samples etc. In state of a human crisis, at crossroads of life literature is always a trusty friend. Literature, the art built on words has a wonderfid mission of helping us through the pitfalls of human life. A poem read in a situation that seems a deadlock can be balm σα our wounds. Books show us the direction to follow by their message and help us to overcome difficulties. This way they can cure us and can be used for restoring the harmony of the human soul.